Stomate-based defense and environmental cues - Panchal, Shweta (Plant Signal Behav, 2017)
Environmental conditions play crucial roles in modulating immunity and disease in plants. For instance, many bacterial disease outbreaks occur after periods of high humidity and rain. A critical step in bacterial infection is entry into the plant interior through wounds or natural openings, such as stomata. Bacterium-triggered stomatal closure is an integral part of the plant immune response to reduce pathogen invasion. Recently, we found that high humidity compromises stomatal defense, which is accompanied by regulation of the salicylic acid and jasmonic acid pathways in guard cells. Periods of darkness, when most stomata are closed, are effective in decreasing pathogen penetration into leaves. However, coronatine produced by Pseudomonas syringae pv. tomato (Pst) DC3000 cells can open dark-closed stomata facilitating infection. Thus, a well-known disease-promoting environmental condition (high humidity) acts in part by suppressing stomatal defense, whereas an anti-stomatal defense factor such as coronatine, may provide epidemiological advantages to ensure bacterial infection when environmental conditions (darkness and insufficient humidity) favor stomatal defense.